Studies in Intercultural Communicative Competence in Language Teacher Education - Guerra, Luis (2020)
The aim of this chapter is to review some of the most relevant research on intercultural communicative competence in English language teaching published since 2000. Fifty-five studies have been examined and information regarding the methodology used, their research aims and themes, and their findings are briefly identified. Moreover, based on the analysis of the studies, three categories of topics of research have emerged: (a) studies on intercultural communicative competence in pre-service teacher training; (b) studies on intercultural communicative competence in in-service teacher training; and (c) studies focused on other major areas of research (i.e. theoretical foundation of intercultural communicative competence, materials/activities/strategies aiming at developing the learners’ intercultural communicative competence and student-based research). It is hoped that novice as well as experienced researchers in the field of English language teaching, in general, and of intercultural communicative competence, in particular, might gain some useful information regarding the most recent research trends in their area of research.